Spectroscopy of gadolinium ion and disadvantages of gadolinium impurity in tissue compensators and collimators, used in radiation treatment planning. Issue 4 (2007) - Maqbool Maqbool, M. M.; Ahmad Ahmad, Iftikhar Iftikhar
Abstract : Intense ultraviolet emission from gadolinium doped amorphous aluminum nitride thin films deposited on Si (111) substrate is studied with cathodoluminescence and photoluminescence. The purpose of the study is to find the merits or demerits of gadolinium ions if added intentionally or present as unintentionally added impurity in tissue compensators or collimators in radiation treatment planning. These films are deposited by reactive sputtering at liquid nitrogen temperature, using 100–200 W RF power, 5–8 mTorr nitrogen, and a metal target of aluminum and gadolinium. Thermal annealing was performed at a temperature of 900 ౨ C. A sharp ultraviolet peak is observed at 314 nm corresponding to 6 P7/2 → 8 S7/2 transition. The ultraviolet emission is intense enough to harm human tissues if it is used as tissue compensator. Intense ultraviolet emission is observable even if the concentration of gadolinium is less than 0.5%. Thermal annealing further enhances the intensity of ultraviolet emission, indicating that longer use of such tissue compensators or collimators containing gadolinium ions will provide more harm and damage to human body. Radiation Therapists, Oncologist and industries making tissue compensators and collimators are strongly suggested to test any compensator or collimator for gadolinium impurities.